Produccion artesanal de semilla de frejol (P. vulgaris L.) - Peralta I., E.; Ortíz Arriola, V.; Koriyama, M. (International Center for Tropical Agriculture, 1991)
Information is given on a small-scale bean seed production project in Ecuador, Peru, and Bolivia as to responsible institutions and technicians, duration, background, justification, objectives, methodology, activity chronogram, description of activities and distribution of responsibilities, expected products and results, and budget by country. (CIAT)